Effect of natural fibers on thermal spalling resistance of ultra-high performance concrete - Zhang, Dong (2022)
It has been established that the addition of synthetic fibers like polypropylene (PP) to ultra-high performance concrete (UHPC) enhances the latter's thermal spalling resistance. The key for this is the thermal mismatch between embedded fibers and matrix as a result of the expansion of PP fibers with temperature. This paper explores the effect of natural fibers (replacing traditional PP fibers) on compressive strength, hot permeability, and spalling resistance of UHPC. Different dosages (3, 5 and 10 kg/m3) of jute fibers are used for this purpose. The findings are critical as they oppose the mechanism of thermal spalling resistance established for synthetic fibers in UHPC. Natural fibers swell by absorbing water (during the casting of UHPC and during their service life) and shrink upon exposure to warm and high temperatures. The deswelling and shrinkage of natural fibers at high temperatures create spaces between fibers and matrix, which could influence permeability at those temperatures. This suggests that percolation of fibers is critical in the case of jute as opposed to PP fibers. It was found that a dosage of 10 kg/m3 of jute fibers is required for eliminating spalling of UHPC as opposed to 3 kg/m3 for PP fibers. Additionally, preliminary efforts are put in to investigate the short-term durability of the samples and changes in properties of UHPC with jute fibers.